Maternal diabetes and risk of multiple sclerosis in the offspring: A Danish nationwide register-based cohort study. (October 2021) - Nielsen, Nete Munk; Gørtz, Sanne; Hjalgrim, Henrik; Rostgaard, Klaus; Munger, Kassandra L; Ascherio, Alberto; Magyari, Melinda; Stenager, Egon; Frisch, Morten
Background: Previous studies suggest a 3- to-10-fold increased risk of multiple sclerosis (MS) in offspring of mothers with diabetes mellitus (DM). Objectives: To examine MS risk in offspring of diabetic mothers, overall and according to type of maternal DM, that is, pregestational DM or gestational DM, as well as to examine MS risk among offspring of diabetic fathers. Methods: The study cohort included all 1, 633, 436 singletons born in Denmark between 1978 and 2008. MS diagnoses were identified in the Danish Multiple Sclerosis Registry, and parental DM diagnoses in the National Patient Register. We used Cox proportional hazards regression analyses to calculate hazard ratios (HRs) with 95% confidence intervals (CIs) for the association of parental DM with MS risk in the offspring. Results: MS risk among individuals whose mothers had pregestational DM was 2.3-fold increased compared with that among individuals with nondiabetic mothers (HR = 2.25; 95% CI: 1.35–3.75, n = 15). MS risk was statistically non-significant among offspring of mothers with gestational DM (HR = 1.03 (95% CI: 0.49–2.16), n = 7) and among offspring of diabetic fathers (HR = 1.40 (95% CI: 0.78–2.54), n = 11). Conclusion: Our nationwide cohort study utilizing high-quality register data in Denmark over several decades corroborates the view that offspring of diabetic mothers may be at an elevated risk of developing MS.